PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN PENANGANAN KONFLIK TERHADAP KINERJA GURU SD NEGERI 19 PONTIANAK UTARA - B31111185, JULIUS (Jurnal Manajemen Update, 2016)
This study, entitled "Effects of Leadership Style Conflict Management Principal and Elementary School Teacher Performance Against 19 in villages upstream pontianak Siantan north." The purpose of this study is a). to determine the effect of Leadership Style The principal of the primary school teachers' performance 19 pontianak north. b). To determine the effect of handling conflicts on teacher performance SD Negeri 19 pontianak north. This research method using descriptive. A population of 30 people. In this study using quantitative analysis using analytical tools test instruments, test classic assumptions and test hypotheses, to test the independent variable on the dependent variable. From the analyst t-test found no significant diffence between the principal’s leadership style variables on the performance of public school teacher 19 pontianak the nort that has a significant probability value of 0,177 > 0,05. The researchers concluded that the duty of a teacher is not dependent on a principal’s leadership style but from other factors not examined in this study, while the handling of the conflict between the variableson the performance of the teacher SD Negeri 19 Pontianak north that has a significant probability value 0,024 < 0.05 there is a positive and significant impact. It proves that a leader who can understand and use their skills to manage conflict so that it can lead to a conducive situation within the organization and improve the performance of the teachers. Keywords: Leadership Styles, Conflict Management, Teacher Performance